El Excentrico, 1967-10-20 - Garcia, Humberto:::Publisher:::::::::::: (Garcia Printing; San Jose, California, 2023)
October 20, 1967 [5 de octubre de 1967]. No volume or issue number. Cover has a photograph Hurricane Beulah victims and a headshot of Frank Campista. The headline reads, "Hurricane Beulah Benefit Dance - Friday, Nov 3 I.E.S Hall, 1401 E. Santa Clara St."